The impact of internet usage among University Students - Mohamad Rahmat Abdul Kadir, . (2012)
This thesis is based on studies on the impact of Internet use among university students. This study was performed to determine the effects of excessive internet use among students. Internet is one of the tools or applications that are often used by students today. In addition to searching for information purposes and general knowledge, the internet is also used as an ingredient for their virtual socializing. From this study, researchers were able to determine whether the Internet can help students in everyday life as a student or otherwise. This study focuses on the impact on a student's own self as well as their academic achievement. Through data collection and questionnaires were distributed, the researchers were able to identify the impact that will be received by a student if using the internet excessively. Through this study, the researchers hope that the students and the public can identify the effects and how to overcome the problem of excessive internet use.